PENERAPAN LATIHAN BATUK EFEKTIF UNTUK MENGELUARKAN SPUTUM PADA PASIEN PNEUMONIA DI RSUD KARAWANG - Lestari, Yumi Dian; Fauzi, Wirdan (Ensiklopedia of Journal, 2023)
Abstract: Pnemonia is marked by coughing withquick breath and or asphyxiation. Shortness of breath that is not solved quicly can result in breath filure and can lead to death Which is why is needs a supportive treatment. One of them is effective cough practice. So it can help the client to release sputum on pneumonia patients. The reason for this research that uses the design quasi – designed non- randomization experiment pre-test-post test group design. Counting t’s for sputum spending before cough practice is effective with p-value 0,000 and for sputum spending after a cough exercise is performed effectively p=value 0,000. The results of statistics can be concluded that there is an effective cough exercise effect on the output of sputum in pneumonia patien. Keywords:Respiratory rate, pneumonia, cough exercises are effec